The efficacy of oxidised regenerated cellulose powder in reducing blood loss during primary total hip arthroplasty: a retrospective cohort study - Pil Whan Yoon; Hong Jin Kim; Jae Youn Yoon; Jun-Ki Moon; Sunhyung Lee (Journal of Orthopaedic Surgery and Research)
Abstract Background Oxidised regenerative cellulose (ORC) is an absorbable haemostatic agent that acts independently on the blood coagulation mechanisms. Although ORC products have been used as adjuncts in various surgical procedures, their haemostatic effect, particularly the powder type (Surgicel®-P), during primary total hip arthroplasty (THA) remains uncertain. This study aimed to evaluate the effectiveness and safety of ORC powder in patients undergoing primary THA. Methods This study included 279 patients who underwent primary THA between January 2022 and July 2024, and they were divided into two groups based on the use of ORC powder: the control (n = 138) and SC (SurgiCel group, n = 141) groups. Data on perioperative outcomes, including operative time, total blood loss (TBL), intraoperative blood loss (IBL), hidden blood loss (HBL), haemoglobin (Hb) drops, and complication rates over 3 months, were collected and compared between the two groups. Results The mean IBL was significantly lower in the SC group (197.1 mL) than in the control group (243.5 mL) (P < 0.001). The total operative time (P = 0.465), procedure time (P = 0.117), TBL (P = 0.167), and HBL (P = 0.771) showed no significant differences. The mean postoperative Hb drop was significantly different between the control and SC groups (1.5 vs. 1.0 g/dL, P < 0.001). Similarly, the mean postoperative day 1 Hb drop was significantly lower in the SC group than in the control group (1.7 vs. 2.0 g/dL, P = 0.013). Complication rates showed no significant differences during the 3-month postoperative follow-up. Conclusions ORC powder significantly reduced IBL and postoperative Hb drops without any comparable complications in patients undergoing primary THA. These findings suggest that ORC powder is a safe and effective haemostatic agent during primary THA procedures, which may be a valuable adjuvant for reducing blood loss and potential to reduce blood transfusion requirements.